Responses of reinforced concrete structures under progressive collapse subjected to different loading methods and loading rates - Pham, Anh Tuan (2017)
A research programme on static and dynamic behaviour of reinforced concrete substructures against progressive collapse subjected to different loading rates, loading configurations, as well as structural types, was conducted. Based on numerical analyses, a semi-analytical approach was proposed to predict static response of beam-column sub-assemblages under single column removal scenario. Thereafter, three sets of experiments were conducted on two-dimensional beam-column frames, namely, (Series I) free-fall dynamic tests under concentrated loading condition, (Series II) quasi-static and free-fall dynamic tests under uniformly distributed loading condition, and (Series III) contact detonation tests under concentrated loading condition. The purpose was to directly compare structural behaviour between quasi-static and realistic dynamic environments, as well as between different loading configurations. Last but not least, an investigation was carried out to study mobilisation of tensile membrane action in beam-slab structures, including the development of a simplified analytical model for the case of internal-column loss.